Virgin Coconut Oil (VCO) Business Analysis in Terms of Economic Income - Gina El Safira; Yuni Sari; Dadang Waluyo (Journal of Economics Business Industry, 2023)
High fluctuations in coconut prices have resulted in coconut farmers in North Minahasa Regency experiencing uncertainty about their economic conditions, so derivative products from coconuts, such as Virgin Coconut Oil (VCO), which can be processed, are needed. This study aims to calculate the feasibility of making Virgin Coconut Oil (VCO), which is processed traditionally, and analyze sensitive indicators from each aspect studied. Traditionally processed Virgin Coconut Oil (VCO) quality highly depends on raw materials and processing. The business feasibility analysis parameters used are marketing, technological, management, legal, and economic. The method used is the Multidimensional Scaling (MDS) Method. The analysis showed that the financial aspect obtained Net Present Value NVP value = IDR 482,378,746, IRR = 93.88%, Gross B/C Ratio = 2.193, PR = 3.64, PBP = 1 year eight days. The feasibility index assessment of five aspects obtained values: marketing aspects 83.50%, technology aspects 52.28%, management aspects 60.91%, legal aspects 65.39%, and economics 74.83%. The average value of the feasibility index shows that the traditional VCO manufacturing business in North Minahasa Regency can be declared feasible.